A Scheme for a state medical service
1941-11 1941 1940s 3 pages Confidential Labour Party R.D.R.31/November, 1941 Public Health Sub-Committee A SCHEME FOR A STATE MEDICAL SERVICE Ultimate Structure A. PRINCIPLES Prevention and cure of disease and maintenance of optimum health. Health Education. Rehabilitation. 1. A complete service, including the provision of surgical appliances, dentures, spectacles, etc.; convalescence; home helps (not only for maternity cases;) midwives, health visitors, welfare workers (to assist in the solution of environmental problems) as well as medical and nursing staffs. 2. Free to all. It is important that no question of ability to pay should deter people from early attendance at the Centres. No insurance basis, flat rate, or payment by assessment would be as satisfactory as a Free Service. In education there is already a precedent for having a vital service free. 3. Open to all. No upper income limit. This should not be a service for the poor but for the entire nation, aimed positively at the improvement and maintenance of the health of the nation. As such the service should not be limited in extent. Nor should it be possible for the public to doubt that the best services are here available. 4. Whole-time doctors, salaried, with fixed hours of service. 5. Research facilities to be available for all medical staff. 6. Industrial Hygiene. All doctors must be concerned in securing healthy conditions of work in factories, shops and offices. They must have authority to ensure that all their reasonable requests are carried out. B. OPERATIONAL UNIT 1. A unit of 100,000 population would be convenient in urban areas (perhaps less in rural areas). All doctors in such an area would be in close personal touch and used to working together. 2. 600 to 1,200 bed hospital near traffic centre of the area. 3. Division Health Centre for specialist consultations in close association with the hospital. 4. Local Health Centres from which a total of about 50 Home Doctors should work in groups of 3 (in scattered areas) to 12. 292/847/1/7